Melanocortin receptor 3 and 4 mRNA expression in the adult female Syrian hamster brain - Hall, Megan A. L.; Kohut-Jackson, Abigail L.; Peyla, Anna C.; Friedman, Gloria D.; Simco, Nicole J.; Borland, Johnathan M.; Meisel, Robert L. (Frontiers in Molecular Neuroscience, 2023)
Melanocortin 3 receptors (MC3R) and melanocortin 4 receptors (MC4R) are vital in regulating a variety of functions across many species. For example, the dysregulation of these receptors results in obesity and dysfunction in sexual behaviors. Only a handful of studies have mapped the expression of MC3R and MC4R mRNA across the central nervous system, with the primary focus on mice and rats. Because Syrian hamsters are valuable models for functions regulated by melanocortin receptors, our current study maps the distribution of MC3R and MC4R mRNA in the Syrian hamster telencephalon, diencephalon, and midbrain using RNAscope. We found that the expression of MC3R mRNA was lowest in the telencephalon and greatest in the diencephalon, whereas the expression of MC4R mRNA was greatest in the midbrain. A comparison of these findings to previous studies found that MC3R and MC4R expression is similar in some brain regions across species and divergent in others. In addition, our study identifies novel brain regions for the expression of MC3Rs and MC4Rs, and identifies cells that co-express bothMC3 and MC4 receptors within certain brain regions.